Enzyme-Linked Immunosorbent Assays Using the Recombinant gp51 and p24 of Bovine Leukemia Virus for Immunodetection of the Disease - Larsen, Alejandra (2017)
Enzyme-linked immunosorbent assay (ELISA) is often used to test bovineleukemia virus (BLV) infection. However, commercially available kits test inSouth America detect only antibodies against the gp51 protein. With the aimto improve the sensitivity of the test, we developed here a two-step indirectdual ELISA test that included both proteins p24 and gp51, expressed andproduced in E. coli and baculovirus expression system respectively. Two hundredten BLV sera, stated as double positive or double negative by the combinationof commercial agar gel immunodiffusion (AGID) assay and a gp51-ELISA test, were tested with our in house dual rp24/rgp51 ELISA. Firstly, we checked the purified, optimized and standardized proteins as antigen by the checkerboard technique, and set up our in house ELISA test. The concordancecorrelation coefficient (CCC) and coefficient of variation (CV) intraplate repeatability levels were within the values established by the international standards.The statistical analysis demonstrated the value of sera correctly rankedhighest (93.48%), and for 0.3 cutoff, the sensitivity was 95.65% and the specificity 91.30%. In conclusion, the rp24/rgp51 ELISA developed and standardized here demonstrated to have good analytical characteristics to be considered for screening of BLV.